Examination of a Parent-Mediated Detect, Practice, and Repair Procedure to Improve Math Fact Fluency. Issue 4 (1st December 2019) - Martin, Ryan J.; Codding, Robin S.; Collier-Meek, Melissa A.; Gould, Kaitlin M.; DeFouw, Emily R.; Volpe, Robert J.
Abstract: Fact fluency is an important prerequisite to mastering more complex and abstract mathematics principles. Delivering math interventions in the home setting may be a feasible way to expose students to necessary supports and improve math outcomes. The present study utilized a multiple baseline design across parent–student dyads to examine the impact of Detect, Practice, and Repair, modified to be implemented by parents in the home environment, on the fluency of basic addition and subtraction facts of 4 second-grade students. Video modeling and performance feedback were used to train and support parents during implementation. Math fact fluency improved across all students, with 2 students reaching mastery levels, and progress was maintained following intervention. Video modeling alone was insufficient for parent training, although performance feedback was effective in improving parents' procedural fidelity. Considerations regarding social validity and suggestions for future research are discussed.